PENGARUH KESENJANGAN PENDIDIKAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS SOSIAL KOTA MAKASSAR - Andi Dwi Wulandari; Muliyadi Hamid; Ilham Safar (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
This study aims to analyze the effect of educational disparity and work motivation on employee performance at the Social Service Office of Makassar City. The study employed a quantitative approach using a survey method. The research population consisted of all 90 employees of the Social Service Office of Makassar City, who were entirely selected as the sample using a total sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The results indicate that educational disparity does not have a significant partial effect on employee performance. In contrast, work motivation has a positive and significant effect on employee performance. Simultaneously, educational disparity and work motivation significantly influence employee performance. The coefficient of determination shows that a substantial proportion of employee performance variation can be explained by the two independent variables, with work motivation identified as the most dominant factor. These findings suggest that improving employee performance in social service institutions can be more effectively achieved by strengthening work motivation, accompanied by continuous management of educational disparities through training and capacity development programs.